Aspirin use after diagnosis but not prediagnosis improves established colorectal cancer survival: a meta-analysis. Issue 9 (19th September 2014) - Li, Peiwei; Wu, Han; Zhang, Honghe; Shi, Yu; Xu, Jinming; Ye, Yao; Xia, Dajing; Yang, Jun; Cai, Jianting; Wu, Yihua
Abstract : Objective: The objective of this meta-analysis was to systematically assess the survival benefit of aspirin use before or after diagnosis for patients with colorectal cancer (CRC). Design: Relevant studies were identified through searching PubMed, Embase and Cochrane databases before May 2014. Two investigators extracted data independently for baseline characteristics and outcomes from the included studies. Either a fixed-effects or a random-effects model was derived to composite the pooled HR for overall mortality and CRC-specific mortality of CRC. Results: Seven studies on postdiagnosis aspirin therapy and seven studies on prediagnosis aspirin use were finally included in this meta-analysis. The overall survival benefit associated with postdiagnosis aspirin use represented an HR of 0.84 (95% CI 0.75 to 0.94). This effect was observed both in colon cancer (HR=0.78, 95% CI 0.64 to 0.96) and in rectal cancer (HR=0.90, 95% CI 0.83 to 0.98). Besides, the survival benefit of postdiagnosis aspirin use appeared to be confined to those patients with positive prostaglandin endoperoxide synthase 2 (PTGS2, also known as cyclooxygenase-2, COX-2) expression (HR=0.65, 95% CI 0.50 to 0.85) and with mutated PIK3CA tumours (HR=0.58, 95% CI 0.37 to 0.90). Aspirin use postdiagnosis was not associated with CRC-specific mortality (HR=0.77, 95% CI 0.52 to 1.14). We observed no evidence of an association between prediagnosis aspirin use and CRC overall mortality (HR=1.01, 95% CI 0.96 to 1.06) or CRC-specific mortality (HR=0.93, 95% CI 0.82 to 1.05). Conclusions: These findings provide further indication that postdiagnosis aspirin therapy improved CRC overall survival, especially for patients with positive PTGS2 (COX-2) expression and mutated PIK3CA tumours.